2020
DOI: 10.1111/jpc.14688
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric pancreatic diseases

Abstract: Paediatric pancreatic diseases are often under‐recognised and may be associated with severe diseases and significant clinical consequences. In recent years, advances have been made in key areas, particularly with the contributions from international societies and study groups focused on paediatric pancreatic disease research. This review focuses on the two key manifestations of pancreatic disorders in childhood, pancreatitis and exocrine pancreatic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This study, which used fasting blood sugar and HbA1c as screening tools, reported one patient (7.1%) with diabetes mellitus, comparable to 4–9% in children with CP from other reports 41,42 . An oral glucose tolerance test is also indicated in patients with CP, 3 particularly when the patients have a pre‐diabetes range of fasting blood sugar or HbA1c levels 41 …”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…This study, which used fasting blood sugar and HbA1c as screening tools, reported one patient (7.1%) with diabetes mellitus, comparable to 4–9% in children with CP from other reports 41,42 . An oral glucose tolerance test is also indicated in patients with CP, 3 particularly when the patients have a pre‐diabetes range of fasting blood sugar or HbA1c levels 41 …”
Section: Discussionmentioning
confidence: 61%
“…Moreover, annually monitoring of fat-soluble vitamins is recommended in patients with CP and should be considered in patients with ARP. 3,41 Four patients were documented with a suboptimal level of the vitamins in this study. However, the monitoring was only available in the last 10 years at our institute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2019; Li et al . 2019), cystic fibrosis (Coffey and Ooi 2020), inflammatory bowel disease (Fofanova et al . 2016), Crohn's disease and irritable bowel syndrome (Gu et al .…”
Section: Human Milk Microbiota: Diversitymentioning
confidence: 99%